Narrow size regime among individuals favors rapid growth in Arctic char ( Salvelinus alpinus) juveniles - Seppä, Teija; Peuhkuri, Nina; Hirvonen, Heikki; Laurila, Anssi; Piironen, Jorma; Ranta, Esa (Canadian Journal of Fisheries and Aquatic Sciences, 1999)
We studied whether social environment in the form of different body size regimes in rearing groups affects the growth of juvenile Arctic char (Salvelinus alpinus) in hatchery conditions. Young-of-the-year Arctic char were divided into groups of three different compositions (a wide, a bimodal, and a narrow size-frequency distribution) in which individuals would be subjected to different dominance and competitive relationships. After a 9-month growth period the fish in the narrow size distribution had grown the fastest in both length and weight. Also, total biomass gains were highest for fish originating from the narrow size distribution treatment. The adjusted mean biomasses for wide, bimodal, and narrow size regime treatments were 5400, 5000, and 5900 g, respectively. Our results give support to the hypothesis that individuals in size-sorted groups should show enhanced growth compared with individuals originating from a wider size-frequency distribution where more aggressive interactions are to be expected.